2016
DOI: 10.3389/fpsyg.2016.01452
|View full text |Cite
|
Sign up to set email alerts
|

Sizing Up Objects: The Effect of Diminutive Forms on Positive Mood, Value, and Size Judgments

Abstract: Language (e.g., structure, morphology, and wording) can direct our attention toward the specific properties of an object, in turn influencing the mental representation of that same object. In this paper, we examined this idea by focusing on a particular linguistic form of diminution used in many languages (e.g., in Polish, Spanish, and Portuguese) to refer to an object as being “smaller.” Interestingly, although objects are usually considered “better” when they are bigger in size, objects described with lingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…The results of Study 3 showed that using diminutives had an adverse impact on the overall evaluation of the candy bar (the pleasure from eating it, tastiness and quality). This result is parallel to the ones obtained in previous studies: tastiness ratings are following the 'bigger is better' heuristic (Parzuchowski, et al, 2016). Nevertheless, the use of a diminutive did not influence the perceived size and price estimations of the candy bar.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The results of Study 3 showed that using diminutives had an adverse impact on the overall evaluation of the candy bar (the pleasure from eating it, tastiness and quality). This result is parallel to the ones obtained in previous studies: tastiness ratings are following the 'bigger is better' heuristic (Parzuchowski, et al, 2016). Nevertheless, the use of a diminutive did not influence the perceived size and price estimations of the candy bar.…”
Section: Resultssupporting
confidence: 88%
“…This explanation is consistent with the notion that the top-down processes do not change the perception per se, but rather influence some higher order processes, for example language processing (Levin & Banaji, 2006;Lupyan, Thompson-Schill, & Swingley, 2010) or memory or coding of information (Firestone & Scholl, 2015). Accordingly, Parzuchowski et al (2016) proposed that what explains the effect of the diminutives is the influence of the linguistic form of the visual representation of the object's size -when using the diminutive form, the recalled exemplars of a given category are smaller than when using the regular form.…”
Section: The Influence Of Diminutives On Cognitionsupporting
confidence: 87%
See 2 more Smart Citations
“…Still, the different patterns of results between Experiment 1 and Experiment 2 do hint at the possibility that different mental mechanisms, or strategies were at stake in these experiments. Applying different strategies when making judgments is reminiscent of the idea that we often make judgments based on simplifying strategies (i.e., heuristics), rather than on extensive algorithmic processing (e.g., Parzuchowski, Bocian, & Gygax, 2016;Kahneman & Tversky, 1996). Indeed, as presented in the introduction, there are numerous other domains in which gender stereotypes influence people's judgments.…”
Section: Social Role Theorymentioning
confidence: 99%